Concomitant administration of radiation with eribulin improves the survival of mice harboring intracerebral glioblastoma. Issue 7 (19th June 2018) - Miki, Shunichiro; Imamichi, Shoji; Fujimori, Hiroaki; Tomiyama, Arata; Fujimoto, Kenji; Satomi, Kaishi; Matsushita, Yuko; Matsuzaki, Sanae; Takahashi, Masamichi; Ishikawa, Eiichi; Yamamoto, Tetsuya; Matsumura, Akira; et al.
Abstract : Glioblastoma is the most common and devastating type of malignant brain tumor. We recently found that eribulin suppresses glioma growth in vitro and in vivo and that eribulin is efficiently transferred into mouse brain tumors at a high concentration. Eribulin is a non‐taxane microtubule inhibitor approved for breast cancer and liposarcoma. Cells arrested in M‐phase by chemotherapeutic agents such as microtubule inhibitors are highly sensitive to radiation‐induced DNA damage. Several recent case reports have demonstrated the clinical benefits of eribulin combined with radiation therapy for metastatic brain tumors. In this study, we investigated the efficacy of a combined eribulin and radiation treatment on human glioblastoma cells. The glioblastoma cell lines U87MG, U251MG and U118MG, and SJ28 cells, a patient‐derived sphere culture cell line, were used to determine the radiosensitizing effect of eribulin using western blotting, flow cytometry and clonogenic assay. Subcutaneous and intracerebral glioma xenografts were generated in mice to assess the efficacy of the combined treatment. The combination of eribulin and radiation enhanced DNA damage in vitro. The clonogenic assay of U87MG demonstrated the radiosensitizing effect of eribulin. The concomitant eribulin and radiation treatment significantly prolonged the survival of mice harboring intracerebral glioma xenografts compared with eribulin or radiation alone ( P < .0001). In addition, maintenance administration of eribulin after the concomitant treatment further controlled brain tumor growth. Aberrant microvasculature was decreased in these tumors. Concomitant treatment with eribulin and radiation followed by maintenance administration of eribulin may serve as a novel therapeutic strategy for glioblastomas. Abstract : Glioblastoma is the most malignant brain tumor for which no effective treatment is currently available. We showed that eribulin is a radiosensitizer and a concomitant eribulin and radiation treatment followed by maintenance eribulin administration significantly prolonged survival of brain tumor‐bearing mice compared with the eribulin or radiation monotherapy. We propose that a combined eribulin and radiation treatment as a new therapeutic strategy for glioblastoma.